Optimization of Cookies Formulation Based on Composite Flour of Sorghum (Sorghum bicolor L), Breadfruit (Artocarpus communis), and Peanut (Arachis hypogaea L.) - Hasnelly Hasnelly; Wisnu Cahyadi; Peggie Haly Al-Fatihah (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2023)
This study investigates the challenges associated with making cookies using wheat flour as the primary raw material. Due to the difficulty in cultivating wheat seeds in the region, alternative sources of flour, such as sorghum, breadfruit, and peanuts, need to be explored to diversify the food supply. Therefore, this study aims to assess the level of the desired characteristics achieved from the composite of sorghum, breadfruit, and peanut flour cookies using the Design-Expert program and the D-optimal Mixture method. To evaluate the responses, chemical, organoleptic, and physical properties are examined, including water content, protein content, fat content, carbohydrate content, color, aroma, texture, taste, and hardness. Furthermore, the optimal formula, generated by the program, contains 23.298% sorghum, 7.869% breadfruit, and 18.843% peanut flour, with an accuracy value of 0.653. The results show that the optimal formula for cookies based on the composite flour has the desired characteristics and complies with the SNI standards 2973-1992 and 2973-2011.